Pengaruh Sistem Kontrol Tidak Langsung Terhadap Hubungan Participation Standard Setting, Standard Tightness, Standard-Based Incentive, Job-Related Stress dan Job Performance - Kiryanto Kiryanto; Sutapa Sutapa (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2005)
The purpose of this research is to test the effect of indirect control system on Participative Standard Setting, Standard Tightness, Standard-Based Incentive, Job-Performance and Job-Related Stress. This research is based on the previous research by Demski and Feltham (1978). The research took samples of public accountants in Central Java and Yogyakarta and the method of data collection is purposive method which collects 67 public accountants. By using path analysis the research shows that three components (Participative Standard Setting, Standard Tightness, Standard-Based Incentive) have significantly effected job performance through job-related stress. Keywords: participative standard setting, standard tightness, standard based incentives, job related stress, job performance, sistem kontrol tidak langsung